Sensor-Based Programming of Central Pattern Generators in Humanoid Robots. (10th April 2013) - Shahbazi, Hamed; Jamshidi, Kamal; Monadjemi, Amir Hasan
In the present article, a method for generating curvilinear bipedal walking patterns is proposed which is able to generate rhythmic and periodic trajectories for a Nao soccer player robot. To do so, a programmable central pattern generator was used which was inspired from locomotion structures in vertebrate animals. In this paper, the programmable central pattern generators were extended and new Equations were added to make a curvilinear pattern for walking Nao robots on a specified circular curve. In addition, some specific Equations were added to the model to control the arms and synchronize them with the movement of the feet. The model uses some sensory inputs to obtain some feedback from the movement and adjust it conforming to the potential perturbations. Input sensory values consist of accelerator values and foot pressure sensor values located on the bottom of each foot. Feedback values can adopt walking to some desired specifications and compensate the effects of some types of perturbations. The proposed model has many benefits including smooth walking patterns and modulation during walking. This model can be extended and used in the Nao soccer player both for the standard platform and the 3D soccer simulation leagues of Robocup SPL competitions to train different types of motions.